Mauritius : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This report discusses Mauritius's Observance of Standards and Codes for the Financial Action Task Force Recommendations for Anti-Money Laundering and special recommendations on Combating the Financing of Terrorism. Mauritius is pursuing a national strategy to diversify its economy into the provision of global financial services by taking advantage of its linkages with both African and Asian economies. Additionally, Mauritius intends to offer new products in Islamic financial services and wealth management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet